The bridge to organic chemistry : concepts and nomenclature - Yoder, Claude H.; Leber, Phyllis A. , 1949-; Thomsen, Marcus W. , 1955- (Wiley, 2010)
Many fundamental concepts must be mastered before a student can make progress in organic chemistry. Nomenclature and Concepts for Organic Chemistry provides a relatively rigorous discussion of organic chemistry's underlying principles, making it easier for the student to grasp organic